Effect of manganese source on manganese absorption and expression of related transporters in the small intestine of broilers. (28th May 2019) - Liao, X D; Wang, G; Lu, L; Zhang, L Y; Lan, Y X; Li, S F; Luo, X G
ABSTRACT: An experiment was conducted to investigate the effect of manganese (Mn) source on Mn absorption and expressions of Mn, amino acid, and peptide transporters in the small intestine of broilers. A total of 320 Mn-deficient 15-day-old Arbor Acres male broilers were randomly assigned to 5 treatments with 8 replicates/treatment and 8 chicks/replicate and fed an Mn-unsupplemented control diet or the control diet supplemented with 110 mg Mn/kg from either MnSO4, or 1 of 3 organic Mn chelates with weak (OW), moderate (OM), or strong (OS) chelation strength for 14 D. The plasma Mn contents were higher ( P < 0.03) in supplemental Mn groups than in the control group, in OS group than in OM group, and in OM group than in OW and MnSO4 groups on day 28. Broilers fed diets supplemented with Mn had higher ( P < 0.02) duodenal divalent metal transporter 1 (DMT1) and ferroportin 1 (FPN1) mRNA levels and FPN1 protein level on both days 21 and 28 than those fed the control diet. Duodenal DMT1 mRNA and protein levels were higher ( P < 0.05) in OM and OS groups than in OW and MnSO4 groups on day 28. The mRNA levels of amino acid transporters [b 0, + -type amino acid transporter 1 (B 0 AT1) and excitatory amino acid transporter 3 (EAAT3)] were higher ( P < 0.0005), and peptide transporter 1 was lower ( P < 0.04) in the ileum than in the duodenum and jejunum; however, Mn source did not affect ( P > 0.05) mRNA levels of amino acid and peptide transporters in the small intestine of broilers. The results from the present study indicate that both DMT1 and FPN1 facilitated Mn absorption, however, the amino acid and peptide transporters might not be involved in the transport of the organic Mn chelates; organic Mn chelates with moderate and strong chelation strength, especially strong chelation strength, showed higher Mn absorption possibly due to enhanced DMT1 expression in the duodenum of broilers.